Jazz talks: representations & self-representations of African American music and its musicians from bebop to free jazz - Mazman, Alper (2010)
The main focus of this thesis is the representation of jazz music and its musicians, and the ways in which American (black and white) critics, novelists, and musicians interpret this music from the development of bebop to free jazz. My aim is to reveal the complexities of the dialogue between white and black representations of jazz, as well as among the self-representations of African American musicians. To this end, I discuss the discourses of jazz that are embedded within the broader cultural, political and ideological debates in this specific period, illustrating how the meaning of jazz is mediated through these conversations. Although jazz talks through the music itself, I argue that the representation of jazz largely depends on who talks about it. The introduction briefly sketches the context of earlier African American writings on music, from Frederick Douglass through the Harlem Renaissance and beyond. Chapter 1 deals with bebop and the ways in which it was seen as more or less expressive of a specific African American consciousness, and how critics shaped the general view of it. Chapter 2 further explores the African American views of music through James Baldwin short story, "Sonny's Blues". Chapter 3 traces the ways in which white writers used jazz for their own ends, focusing on some key terms such as 'hip' and 'cool'. Chapter 4 explores the complex relation between jazz and the new politics of black liberation through a number of key albums and figures, while Chapter 5 gives a more extended examination of these ideas through the figure of Charles Mingus. My conclusion attempts to look again at one of the themes of the thesis - who has the power to represent jazz - through a discussion of Ken Burns' Jazz.